Influential Factors on Intracanal Post Selection for Endodontically Treated Teeth in Kurdistan Province of Iran - Younesi Baneh, Payam; Kebriyaei, Elaahe; Mahboubi, Shiva (Galen Medical Journal, 2024)
Background: Due to severe coronal destruction, endodontically treated teeth (ETT) often require intracanal posts to provide retention for the restorative material. This study aimed to evaluate the opinions and practices of Iranian dentists regarding the selection of intracanal posts for ETT reconstruction. Materials and Methods: This cross-sectional study was conducted among dentists in Kurdistan province, a region of west of Iran, who have experience in performing ETT reconstruction. A questionnaire was designed, comprising two parts: the first part collected demographic information. The second part assessed the criteria for selecting post systems for ETT, including 12 questions that inquired about the placement of intracanal posts, indications for post placement, post material preferences, post length and diameter, and fabrication methods. Collected data were coded and analyzed using SPSS version 20 (IBM Corp., Armonk, NY, USA). Results: Totally, 96.6% of the participants used posts for ETT. They believed that not all ETT require a post. Also, 53.8% believed that posts do not reinforce ETT; 83.8% mentioned the remaining tooth structure to be the main criterion in choosing between prefabricated and cast posts and cores. Cast posts and cores were used in 62.4% of anterior and 56.4% of posterior teeth. Prefabricated metal posts were used by 68.3% of dentists. Also, 51.3% used base metal alloys for the cast posts and cores; 44.4% stated that at least 4 mm of gutta-percha must remain at the apex, and 45.3% stated that the post diameter should be one-third of the root diameter. Conclusion: The study found that Iranian dentists have varying opinions and practices regarding the selection of intracanal posts for endodontically treated teeth reconstruction, with a preference for cast posts and cores and base metal alloys, and consideration of remaining tooth structure as the main criterion for post selection.